2015
DOI: 10.1177/0886260515605298
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, Nature, and Correlates of Hate Crime Victimization Experiences in an Urban Sample of Lesbian, Gay, and Bisexual Community Members

Abstract: The present study examines two central research questions. First, we sought to add to current knowledge on the frequency and types of hate crime experiences in an urban sample. Also, drawing on existing frameworks for sexual minority specific (SMS) stress, we examined internalized SMS stress (defined by internalized homophobia and acceptance concerns regarding one's minority status) as a mediator of the association between hate crime victimization (i.e., objective or social SMS stress) and mental health sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 30 publications
4
23
1
Order By: Relevance
“…Several studies have examined the degree of homophobia in heterosexual individuals [14,[23][24][25][26][27][28][29][30][31][32] and the degree of internalized sexual stigma in homosexual individuals [33,34]. In particular, high rates of perceived and experienced stigma have been reported by lesbian women and gay men [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have examined the degree of homophobia in heterosexual individuals [14,[23][24][25][26][27][28][29][30][31][32] and the degree of internalized sexual stigma in homosexual individuals [33,34]. In particular, high rates of perceived and experienced stigma have been reported by lesbian women and gay men [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, high rates of perceived and experienced stigma have been reported by lesbian women and gay men [27][28][29][30][31]. Perceived stigma seems to be associated with negative consequences with respect to physical and mental health in sexual minorities [31,35], as well as with low self-esteem [36].…”
Section: Introductionmentioning
confidence: 99%
“…The types of crimes that were highlighted in their responses are also in line with what other studies have found, such as with violent crimes and property crimes (Browning et al, 2017;Chang, 2017;Easter, 2017). None of the respondents mentioned anything about any type of hate crime committed against them, so this was not in line with what was discussed earlier in the articles about the prevalence of hate crimes across Los Angeles Burks et al, 2018;Stotzer, 2008;Stotzer, 2010). An additional study specifically looking at crimes committed against LGBT residents could help to better highlight this particular problem.…”
Section: Discussionmentioning
confidence: 52%
“…Women living in urban areas generally have higher rates of fear of being victimized than men generally do (Riger & Gordon, 1983). There are various reasons for this, but much of it has to do with inequitable power in society, financial dependence, lack of social control, and living with the perceived (or actual) threat of male violence (Burks et al, 2018;Chang & Lau, 2016;Riger & Gordon, 1983). Some individuals are at increased risk of being victimized due to their positions in the social structure, their lifestyles, their social status, their living situations, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation